Resort Architecture in Regional Perceptions: Multiple Aspects of a Region in Iván Kotsis' Design Method for Balaton Lakeshore (Prostor, 2021)
The regional aspirations of resort architecture give specific perspectives on the history of regionalism. The development of the shores of Lake Balaton, the largest lake in Central Europe, was determined by this particular regional aspiration. Iván Kotsis was a defining figure of Hungarian architecture between the world wars, and had a significant impact on the period - not only with his work as an architect, but also as a university professor and a public activist. This paper examines his activity around Lake Balaton on different scales, since it represented a peculiar perspective within the history of regional ideas. The research concludes that Kotsis’ regional perspective focused on resort architecture was an independent conception separated from both modern and local interpretations. Based on his university work and the knowledge transfer resulting from his international relations, he developed an integrated perspective on the region from an academic position. Reflecting on the problems of holiday resorts, he formed an autonomous method with which he experimented, to mediate between the universal modern approach and the local features of the landscape.